The Influence Of Facebook Marketing On Consumer Buying Intention Of Clothing: Evidence From Young Adults - Bernard, D. T. Kingsley; Munasinghe, A. A. S. N.; Premarathne, I. K. R. J.; Wijayarathne, S. (Archives of Business Research, 2020)
As a result of the rapid improvements paved through global advertising pathways, marketers have started to promote their products through social media platforms and among that; Facebook had become the most popular mode of communicating out of all. The study was conducted with the objective of comprehensively investigating the influence of Facebook marketing on consumer buying intention of clothing using evidence of young adults. Predominantly, the research focused upon identifying the superiority of Facebook as a social media communication platform and its relevant impact upon advertising. Majority of the businesses aims toward increasing the reach, whereas Facebook users expect clear experience through Facebook rather than watching typical pop ups, web banners and adds. However, Facebook marketing was identified to be positively and negatively influencing the companies and users. Therefore, focus was to analyze the impact to consumer’s buying intention from Facebook marketing. The companies can identify the effectiveness of the advertising and the improvement to be done. The study has undertaken a comprehensive survey to achieve the objectives of the research and those data was analyzed through component factor analysis, regression analysis and correlation coefficient. As per the results of the analysis, researchers have accomplished the stated objectives of the study. In conclusion, it was identified that there was a strong relationship between independent and dependent variables except E-WOM. Among that, Likes and sharing are the most important variables in Facebook marketing. According to outcomes, E- WOM was not an important variable, nonetheless researchers recommend focusing on E-WOM in order to convert this variable in to positive way to make better results, as previous researches stated that E-WOM can make massive impact to consumer purchase intention.